Assessing the utility of retailer based on generalized costs of end-consumers - Andrii Halkin (Foundations of Management, 2020)
This paper gives a methodology to estimate the generalized costs of end-consumers visiting any retailer. The attractiveness and utility of retailers for end-consumers have been calculated based on their possible generalized costs according to their choice. According to the developed model, analysis of the consumer market visiting all shops in the described zone has been made. Research provides explanation of generalized costs of end-consumers. Generally, the utility function of end-consumers visiting retailers depends on the price and non-price factors. The regression models describing the time spent on transit to a retailer and inside of it provide monetary assessment of costs associated with the purchase process. The monetary level of fatigue was evaluated using the calories spent during the purchase process. The attractiveness of the retailer in an urban zone was assessed as an inverse function of the generalized costs.
Keywords: M30; M31; M39; L66; 650; end-consumers; zone; non-linearity factor; slope factor; generalized costs